Mismatch uracil DNA glycosylase (Mug) is maintained in the Corynebacterium pseudotuberculosis genome and exhibits affinity for uracil but not other types of damage - Bruno Carvalho Resende; Cássio Siqueira Souza Cassiano; Diego Lisboa Rios; Thalia Queiroz Ladeira; Vasco Ariston Carvalho Azevedo; Luciana Lara dos Santos; Lucía Valenzuela-Pérez; Gonzalo Cabrera; Carlos Renato Machado; Débora de Oliveira Lopes (Genetics and Molecular Biology)
Abstract The genome of Corynebacterium pseudotuberculosis, etiologic agent of Caseous Lymphadenitis (CLA), was sequenced to comprehend its genetics, pathogenicity, and virulence mechanisms due to its economic importance. A focus was placed on the G/U mismatch-specific DNA glycosylase (Mug), an enzyme vital for base excision repair in DNA that can play an important role in uracil repair, since the high G+C content of C. pseudotuberculosis makes it prone to deamination events, accentuating the potential significance of Mug. Through in silico and in vitro analyses, the Corynebacterium pseudotuberculosis Mug protein (CpMug) was characterized to confirm its DNA glycosylase activity and lesion affinity. The mug gene was identified in both pathogenic and non-pathogenic Corynebacterium species, lacking a discernible ancestry pattern. Bioinformatics analyses revealed the preservation of essential uracil DNA glycosylase catalytic residues in CpMug. The 3D structure of CpMug was constructed, and molecular docking analysis demonstrated its interaction with DNA containing uracil and other lesions. Comparative analyses revealed a higher affinity of CpMug’s catalytic residues for uracil over other DNA lesions and enzymatic assays with purified CpMug affirmed its uracil DNA glycosylase activity, while it exhibited no activity on 8-oxoguanine, tetrahydrofuran, or thymine glycol, consistent with computational simulations.